Anti-inflammatory and anti-hyperalgesic effects of Ardisia crispa Thunb. D.C - Abd Hamid @ Abdul Razak, Roslida; Kim, Kah Hwi (Wolters Kluwer - Medknow Publications and Media, 2008)
Ardisia crispa Thunb D.C (Myrsinaceae), has long been used in treating various ailments among the local villagers. The objective of this study was to investigate experimentally the possible anti-inflammatory and anti-hyperalgesic properties of Ardisia crispa. The effect of hexane fraction of ethanolic extract of root of Ardisia crispa (ACRH) was evaluated in experimental models of pain and inflammation. The root extract at 3-300 mg/kg showed significant inhibition in carrageenan-induced oedema in rats with a maximum of 93.34% at 300 mg/ kg. There was a significant (p<0.001) inhibition in carrageenan-induced hyperalgesia with ACRH 30, 100 and 300 mg/kg. The anti-inflammatory observed with the extract were comparable to that of standard. The present study indicates that the hexane fraction of Ardisia crispa (ACRH) exhibits significant anti-inflammatory and anti-hyperalgesic effects.